Improving The Mathematical Problem Solving Ability of Students in Class VIII-10 of SMP Negeri 9 Kendari Using Problem-Based Learning Models - Mira Sri Setyowaty (Amanah: Jurnal Amanah Pendidikan dan Pengajaran, 2023)
This study aimed to improve the implementation of learning through a problem-based learning model and improve the mathematical problem-solving abilities of class VIII-10 students of SMP Negeri 9 Kendari through the application of a problem-based learning model. This research is Classroom Action Research which is descriptive qualitative in nature, and the subjects are students of class VIII-10 SMP Negeri 9 Kendari. This research was conducted in two cycles, each consisting of two meetings. Each cycle includes the stages: planning, action implementation, observation/evaluation, and reflection. The results of this study indicate that in the problem-based learning model, students' mathematical problem-solving abilities can be improved. This is indicated by an increase in the implementation of learning and students' mathematical problem-solving abilities. In the implementation of learning, that is, in the first cycle, learning was carried out at 81.61%, increasing in the second cycle, 97.33% was implemented. In terms of students' mathematical problem-solving abilities increased from the initial test, that is, out of 37 students, only 3 students or 8.108% of students who had achieved KKM scores increased in cycle I test results to 20 students or 54.05% of students who achieved KKM scores and increased again in cycle II to 34 students or 91.89% of students who had achieved the KKM